The Effect of Sales Growth, Return on Assets, Firm Size and Fixed Asset Intensity on Tax Avoidance - Adzra, Salsabila Safa; Kurniawati, Lintang (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2025)
Tax avoidance is an important issue in corporate taxation because it reflects how companies manage their tax obligations while remaining within legal boundaries. A firm’s choice to engage in tax avoidance can reveal much about its overall conduct and governance standards. Using a quantitative methodology, this research examines how sales growth, return on assets, firm size, and fixed asset intensity relate to tax avoidance in food and beverage firms on the Indonesia Stock Exchange from 2021 to 2024. A purposive sampling process yielded 123 observational data points, which were processed with SPSS. Findings shed light that both increased sales growth and higher return on assets reduce tax avoidance, implying that growing, profitable companies may adopt more compliant tax practices. In contrast, neither firm size nor fixed asset intensity showed a meaningful impact, revealing that neither scale nor the proportion of fixed assets significantly drives avoidance behavior. These findings imply that tax avoidance practices are more closely related to company performance dynamics than to asset size or composition. Therefore, companies are encouraged to integrate tax strategies within transparent and responsible governance frameworks to minimize compliance and reputational risks.